KEADILAN RESTORATIF DALAM SISTEM PERADILAN PIDANA SEBAGAI PERWUJUDAN NILAI-NILAI PANCASILA - Akbar, Muhammad Fatahillah (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
Pancasila is the ground fundamental norm as the ultimate source of law in Indonesia. Based on that concept, the establishment of National Legal System shall be based on values contained in the Pancasila. One of the reforms of legal system is the establishment of restorative justice. Restorative justice is the concept where in solving criminal law matters, all related parties shall be involved. Restorative justice is the implementation of Pancasila values in the criminal justice system. The problems discussed in this paper is the urgency restorative justice concept in criminal justice system in reflecting Pancasila values. In terms of existing regulation, restorative justice is merely regulated in The Act of Juvenile Justice System (UU SPPA), the Police Commissioner’s Regulation Number 6 of 2019, and the General Attorney Regulation Number 5 of 2020. However, the implementation in practices, restorative justice still has many weaknesses, including the diversion provision. By discussion restorative justice and Pancasila, it can be stated that restorative justice aims to create social justice for everyone involved in a criminal law case and form a cultural mediation in the system. In short, restorative justice is one of crucial concepts in implementing Pancasila values.